An antibiotic recipe for an arrhythmic disaster - McCutcheon, Keir (Cardiovasc J Afr, 2015)
We describe the case of a patient who developed torsade de pointes during temporary pacemaker insertion after administration of intravenous erythromycin. The case highlights the dangers of administering drugs that prolong the QT interval in patients with complete atrioventricular block, and we discuss the underlying pathophysiological recipe that can lead to a potential arrhythmic disaster.